PENERAPAN SANKSI PIDANA TERHADAP PELAKU PERDAGANGAN MANUSIA DALAM PUTUSAN NOMOR 1498/Pid.Sus/2015/PN.Mks - Sampurna, Jafrhan Dharma; Koswara, Indra Yudha (Universitas Muhammadiyah Ponorogo, 2024)
Indonesian people are often involved in human trafficking, which endangers social security and endangers the country. This article discusses the regulation of human trafficking in Indonesia, specifically the Human Trafficking Law. The aim of this research is to determine the causes of human trafficking in accordance with applicable regulations and the application of sanctions in the legal system. This research method uses a normative juridical approach which looks at problems from the study of legal materials such as books or articles that discuss human trafficking as a reference for basic materials and secondary legal materials. The results of this research are that human trafficking is rampant in various countries, including Indonesia and developing countries, where this has become a concern of the world, especially the UN. Human trafficking is a criminal offense, especially as regulated in the Criminal Code. In Indonesian criminal law, it is regulated by Law Number 21 of 2007, the application of sanctions is punishable by imprisonment and fines. Human trafficking is an organized and systematic crime, where the people involved have personal or group interests in making a profit.